EARLY LANGUAGE DEVELOPMENT FROM A PERSONAL PERSPECTIVE - Lock, Andrew J. (Anales de Psicología / Annals of Psychology, 2026)
Early language development is taken as predicated on separable component skills, rather than a single module. These skills are constructed in the course of social interaction between infants and their caretakers. These social interactions function to give a meaningful structure to the infant's developing perception of its "lived-inreality, and it is this structuring of perception through joint interaction with an adult that mediates the elaboration of the component skills. The "giving of meaning to perception" depends on the ways in which adults, in their interactions with their infants, act to draw the infant's attention to aspects of their current situation. Social interaction is, then, fundamentally involved in cognitive and linguistic development.